Parenteral omega-3 fatty acids: pouring oil on troubled waters? - Calder, Philip C (BioMed Central, 2012)
A meta-analysis of parenteral fish oil in 23 studies in intensive care unit (ICU) and non-ICU patients reported a reduced infection rate (significant in ICU patients) and shorter lengths of ICU and hospital stays (both non-ICU and ICU patients). Parenteral fish oil reduced inflammation and improved oxygenation index and liver function. The findings of the meta-analysis are discussed in this report.